A new era for electron bifurcation. (December 2018) - Peters, John W; Beratan, David N; Bothner, Brian; Dyer, R Brian; Harwood, Caroline S; Heiden, Zachariah M; Hille, Russ; Jones, Anne K; King, Paul W; Lu, Yi; Lubner, Carolyn E; Minteer, Shelley D; et al.
Highlights: Electron bifurcation couples endergonic and exergonic electron transfer reactions. Electron bifurcation requires redox sites capable of managing single and pairwise electron transfer reactions. Redox centers in electron bifurcating enzymes exist with an inherently short-lived low-potential redox state. Crossed potential redox transitions have been observed at electron bifurcating sites, but are not required for electron bifurcation. Electron bifurcation catalysis can occur at organic and potentially at inorganic cofactors that undergo at least two redox transitions. Graphical abstract: Simple diagram of electron bifurcation illustrating the bifurcation of an electron pair from the electron donor (D) and the subsequent endergonic and exergonic electron transfers acceptors A1 and A2 respectively. Abstract : Electron bifurcation, or the coupling of exergonic and endergonic oxidation-reduction reactions, was discovered by Peter Mitchell and provides an elegant mechanism to rationalize and understand the logic that underpins the Q cycle of the respiratory chain. Thought to be a unique reaction of respiratory complex III for nearly 40 years, about a decade ago Wolfgang Buckel and Rudolf Thauer discovered that flavin-based electron bifurcation is also an important component of anaerobic microbial metabolism. Their discovery spawned a surge of research activity, providing a basis to understand flavin-based bifurcation, forging fundamental parallels with Mitchell's Q cycle and leading to the proposal of metal-based bifurcating enzymes. New insights into the mechanism of electron bifurcation provide a foundation to establish the unifying principles and essential elements of this fascinating biochemical phenomenon.